Tumor necrosis factor receptor superfamily member 25 (TNFRSF25) agonists in islet transplantation: Endogenous in vivo regulatory T cell expansion promotes prolonged allograft survival. Issue 4 (12th January 2022) - Marfil‐Garza, Braulio A.; Pawlick, Rena L.; Szeto, Jake; Kroger, Charles; Tahiliani, Vikas; Hefler, Joshua; Dadheech, Nidheesh; Seavey, Mathew M.; Wolf, Jeffrey; Jasuja, Rahul R.; James Shapiro, A. M.
Abstract : Regulatory T cells (Tregs) modulate alloimmune responses and may facilitate minimization or withdrawal of immunosuppression posttransplant. Current approaches, however, rely on complex ex vivo Treg expansion protocols. Herein, we explore endogenous in vivo Treg expansion through antibody‐mediated agonistic stimulation of the tumor necrosis factor receptor superfamily member 25 (TNFRSF25) pathway and its potential to prolong graft survival in a mouse model of islet allotransplantation. C57BL/6 male mice were treated with a single dose of TNFRSF25 agonistic antibodies (4C12 or mPTX‐35) or IgG control. Diabetes was induced using streptozotocin. Four days later, flow cytometry was completed to corroborate Treg expansion, and 500 islets (CBA/J male mice) were transplanted. Glycemia was assessed thrice weekly until rejection/endpoint. Early intra‐graft Treg infiltration was assessed 36 h posttransplant. TNFRSF25 antibodies enabled pronounced Treg expansion and treated mice had significantly prolonged graft survival compared with controls ( p  < .001). Additionally, the degree of Treg expansion significantly correlated with graft survival ( p  < .001). Immunohistochemistry demonstrated marked Treg infiltration in long‐term surviving grafts; intra‐graft Treg infiltration occurred early posttransplant. In conclusion, a single dose of TNFRSF25 antibodies enabled in vivo Treg expansion, which promotes prolonged graft survival. TNFRSF25‐mediated in vivo Treg expansion could contribute to achieving lasting immunological tolerance in organ transplantation. Abstract : In a preclinical islet transplantation model, antibody‐mediated agonistic stimulation of the Tumor Necrosis Factor Receptor Superfamily Member 25 induces pronounced in vivo T regulatory cell expansion and promotes prolonged allograft survival.